Atomically Thin Transition‐Metal Dichalcogenides for Electrocatalysis and Energy Storage. Issue 11 (22nd September 2017) - Duan, Xiaochuan; Xu, Jiantie; Wei, Zengxi; Ma, Jianmin; Guo, Shaojun; Liu, Huakun; Dou, Shixue
Abstract: Since the discovery of graphene in 2004, research on 2D materials has grown rapidly. Compared to their bulk counterparts, 2D atomically thin, layered transition‐metal dichalcogenides (TMDCs or MX2 ) nanosheets exhibit excellent electronic and optical properties, outstanding mechanical flexibility, and exceptional catalytic performance. As a representative of 2D materials, MX2 holds great promise in many potential applications, especially in energy‐related applications. Here, a brief overview of atomically thin layered MX2 nanosheets applied in energy storage and conversion systems is presented. Firstly, the crystal structures and phases, morphologies, and synthesis methods of MX2 are discussed. Sequentially, the achieved progress on atomically thin MX2 in energy‐related applications (i.e., the hydrogen‐evolution reaction, oxygen‐evolution reaction, CO2 electrochemical reduction, electrochemical capacitors, lithium‐ion batteries, sodium‐ion batteries, and lithium–sulfur batteries) is systematically discussed. Finally, the conclusions and some prospects regarding atomically thin MX2 for applications in the field of energy‐storage systems are provided. Abstract : Two‐dimensional atomically thin layered transition‐metal dichalcogenides exhibit excellent electronic and optical properties, outstanding mechanical flexibility, and exceptional catalytic performance. An overview of the structures, structure classification, synthesis procedures, and practical applications in energy‐conversion systems of atomically thin layered transition‐metal dichalcogenides is presented.